PENGEMBANGAN MODUL BERBASIS HOTS TERINTEGRASI KARAKTER ISLAMI MATERI PERPINDAHAN KALOR KELAS VA SD MUHAMMADIYAH BAYAN - Titis Reniat; Titi Anjarini; Nur Ngazizah (Jurnal Binagogik, 2024)
This research aims to develop and determine the feasibility of an integrated hots-based module with Islamic characters in heat transfer material for the VA class at Muhammadiyah Bayan Elementary School. The research model used is R&D (Research and Development), with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method. The subjects of this research were VA class students with a total of 19 students. Data collection techniques through interviews, questionnaires and tests. Data acquisition calculates validity, practicality and effectiveness analysis. Validity assessment results from material expert validation with an average of 3.80, percentage 94.05%, media experts with an average of 3.65, a percentage of 88.16%, and learning practitioners with an average of 3.98, achieving a percentage of 98.53%. so it falls within the very valid criteria. Practicality was obtained from student response questionnaires and the implementation of learning on integrated hots-based modules with Islamic characters in limited trials and extensive trials. The results of the students' response to the limited trial were 3.77 percentage 94.17%, the response to the broad test was 3.74 percentage 93.45% while for the implementation of learning the limited trial average was 3.81 percentage 93.75% and the extensive trial an average of 3.96, a percentage of 98.44% based on the results included in the very practical criteria. The effectiveness of the limited n-gain test scored 0.77 and the broad n-gain test scored 0.79. Furthermore, the assessment of cultivating Islamic character attitudes for the limited test averaged 3.67 and 3.70 for the wide trial with these results entering the criteria for being very effective. Based on the results of this data analysis, it can be concluded that the integrated hots-based module with Islamic characters is declared suitable for use in learning.